الفجوة الغذائية العربية من الحبوب في ظل تقلبات أسعار الغذاء العالمية بين عامي (2000-2008) - أبا زيد, ثناء; زيتي, إياد بدر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعتبر الفجوة الغذائية العربية واحدة من أكثر القضايا الاقتصادية الحساسة في الواقع العربي الراهن، حيث يلاحظ اتساع هذه الفجوة باطراد من سنة إلى أخرى، حيث وصلت قيمة هذه الفجوة إلى مستويات حرجة و قدّرت المنظمة العربية للتنمية الزراعية قيمة الفجوة الغذائية في الوطن العربي بحوالي 29.863 مليار دولار عام 2008, شكلت فجوة الحبوب منها أكثر من 61% لنفس العام. سنعمد في هذه الدراسة إلى عرض واقع أسعار الحبوب العالمية بين عامي (2000-2008) وبيان الأسباب التي أدت إلى طفرة الأسعار خلال الفترة (2007/2008), بالإضافة إلى عرض واقع إنتاج الحبوب واستهلاكه في الوطن العربي وبيان العجز الغذائي منه, ثم دراسة معاملات الارتباط بين تطور الفجوة الغذائية من الحبوب من جهة وبين كل من مستوى السعر العالمي لمجموعة الحبوب الغذائية ومعدل النمو السكاني وتطور نصيب الفرد من الناتج المحلي الإجمالي من جهة أخرى. ثم سنقوم في المرحلة الأخيرة بإيجاد نماذج تنبؤية لكمية العجز الغذائي العربي من الحبوب خلال سنوات العقد القادم. Arab food gap is considered one of susceptible economical issues in the Arabic status quo, where anyone can notice the expansion of this gap by time. The value of this gap has reached to critical levels, where Arab Organization for Agriculture Development (AOAD) guessed that the Arab food gap value in 2008 is nearly 29.863 Billion dollars. The cereals gap formed about 61% of the whole gap value. We will show in this study the international cereals prices situated between (2000-2008), and the reasons that caused capering in prices through (2007/2008), in addition to showing Arab production and consumption of cereals and then calculating the Arab deficit of it. Then, we will study correlative relations between the value of Arab food gap of cereals and each level of international cereals prices and evolution of Arab population number and evolution of individual allowance of Arab's (GDP). Finally, we will find predicting patterns of Arab cereals deficit during the coming decade.